Non-invasive assessment of arterial pulsatility in patients with continuous-flow left ventricular assist devices - Cross, Troy J; Sajgalik, Pavol; Fabian, Vratislav; Matera, Lukas; Kushwaha, Sudhir S; Maltais, Simon; Stulak, John M; Schirger, John A; Johnson, Bruce D (The International Journal of Artificial Organs, 2020)
INTRODUCTION: Long-term use of continuous-flow left ventricular assist devices may have negative consequences for autonomic, cardiovascular and gastrointestinal function. It has thus been suggested that non-invasive monitoring of arterial pulsatility in patients with a left ventricular assist device is highly important for ensuring patient safety and longevity. We have developed a novel, semi-automated frequency-domain-based index of arterial pulsatility that is obtained during suprasystolic occlusions of the upper arm: the 'cuff pulsatility index'. PURPOSE: The purpose of this study was to evaluate the relationship between the cuff pulsatility index and invasively determined arterial pulsatility in patients with a left ventricular assist device. METHODS: Twenty-three patients with a left ventricular assist device with end-stage heart failure (six females: age = 65 ± 9 years; body mass index = 30.5 ± 3.7 kg m-2) were recruited for this study. Suprasystolic occlusions were performed on the upper arm of the patient's dominant side, from which the cuff pressure waveform was obtained. Arterial blood pressure was obtained from the radial artery on the contralateral arm. Measurements were obtained in triplicate. The relationship between the cuff pressure and arterial blood pressure waveforms was assessed in the frequency-domain using coherence analysis. A mixed-effects approach was used to assess the relationship between cuff pulsatility index and invasively determined arterial pulsatility (i.e. pulse pressure). RESULTS: The cuff pressure and arterial blood pressure waveforms demonstrated a high coherence up to the fifth harmonic of the cardiac frequency (heart rate). The cuff pulsatility index accurately tracked changes in arterial pulse pressure within a given patient across repeated measurements. CONCLUSIONS: The cuff pulsatility index shows promise as a non-invasive index for monitoring residual arterial pulsatility in patients with a left ventricular assist device across time.
Keywords: asistovaná cirkulace; srdeční selhání; Aged; pulz; arterie; lidé středního věku; Heart-Assist Devices; senioři; Heart Failure; lidé; Reproducibility of Results; Middle Aged; Diagnostic Techniques, Cardiovascular; Blood Pressure; Pulse; reprodukovatelnost výsledků; Female; Arteries; Pulsatile Flow; Assisted Circulation; Male; ženské pohlaví; Humans; podpůrné srdeční systémy; mužské pohlaví; krevní tlak; diagnostické techniky kardiovaskulární; pulzatilní průtok